Literary History, Modernism, and Postmodernism : (The Harvard University Erasmus Lectures, Spring 1983). - Fokkema, Douwe W. (John Benjamins Pub. Co., 1984)
In these lectures, delivered at Harvard University in March 1983, the differences between Modernism and Postmodernism are discussed in semiotic terms, based on a contrastive analysis of semantic and syntactical (compositional) features. They present the major results of research into the literary conventions of Modernism (Gide, Larbaud, V. Woolf, du Perron, Th. Mann) and the innovations of Postmodernism (Borges, Fuentes, Barthelme, Calvino, Hermans). The investigation of innovation in literary history is based on a concept of literary evolution, launched by the Russian Formalists and elaborate.